Biological effects of munition left on sunken war ships in the North Sea: a multi-biomarker study using caged blue mussels and fish caught at WWII wreck sites at the Belgian coast - Binder, Franziska Isabell; Bünning, Lillian Tabea Hannah; Strehse, Jennifer Susanne; Van Haelst, Sven; De Rijcke, Maarten; Maser, Edmund; Brenner, Matthias (Frontiers in Marine Science, 2025)
The environmental risks associated with dumped munitions, unexploded ordnance (UXO) and sunken war ships is gaining more and more attention nowadays, since these warfare materials may start leaking, posing a threat to marine wildlife. This study aims to assess the effects of pollution by explosives for marine fauna associated with sunken war ships still loaded with munitions at the time of sinking. For this purpose, transplanted blue mussels (Mytilus edulis) and passive samplers were exposed for several weeks on two WWII warship wrecks (HMS Basilisk and V1302, formerly named John Mahn) to detect leakage of explosives and to characterize the effects of those substances on mussel health. In addition, fish (Trisopterus luscus) dwelling at V1302 were caught and investigated following the same approach as used with the mussels. The hazardous potential of dissolved explosives was assessed using multi-biomarker analysis, which includes the enzyme activity of catalase (CAT), glutathione S-transferase (GST) and acetylcholinesterase (AChE), as well as histochemical biomarkers like lysosomal membrane stability (LMS), lipofuscin (LIPF), neutral lipids (NL) and glycogen (GLY) as an indicator of mussel’s energy reserve. Chemical analysis of passive samplers as well as mussel and fish tissue indicated leakage of explosives at both wrecks and a subsequent uptake by exposed organisms. The leakage of explosives was correlated with membrane impairments and signs of oxidative stress measured in exposed mussels and fish.